Assessing a rural community-based entrepreneurship in Malaysia: are we there yet? / Rohana Ngah, Mohd Ali Bahari Abdul Kadir and Noor Faizah Mohd Lajin - Ngah, Rohana; Abdul Kadir, Mohd Ali Bahari; Mohd Lajin, Noor Faizah (Universiti Teknologi MARA, Shah Alam: Malaysian Academy of SME and Entrepreneurship Development (MASMED), 2022)
This article draws upon research undertaken in two rural communities in Malaysia under the program My Village My Future, a community-based entrepreneurship program initiated by the government to develop rural areas. Little is known about the success of rural community-based entrepreneurship. The paper uses various community-based entrepreneurship models to explore rural community-based entrepreneurship's roots, challenges, and issues. This study aims to explore the suitable model of community-based entrepreneurship in rural areas. This paper follows a case study method of a narrative approach to analyse community-based entrepreneurship in rural areas. The narrative approach allows the flow of important information from various sources. The results showed that the implementation and success of community-based entrepreneurship programs in rural areas depend on the government's active intervention and strong leadership. Young local leaders must be groomed to spearhead and capture entrepreneurial-driven opportunities and encourage active community participation and a sense of ownership. The study focuses on two communities selected under particular government community-based entrepreneurship programs in rural areas. Therefore, the results may not be generalisable to other contexts. Government intervention is necessary in helping the community to get involved in entrepreneurship. However, the sense of ownership and well-trained local young leaders would help sustain the program in the long term. The government assistance should escalate the community to react quickly and eventually allow them to be independent. Good community leaders play a vital role in sustaining the initiative. In addition, community members must be trained to have an entrepreneurial mindset in creating and sustaining community-based entrepreneurship initiatives. The paper provides insights into rural community-based entrepreneurship, which the government initiated, and how the community can explore further in the long run.